A Study of Water Quality of Bolgoda North Lake - Gunatilaka, W.M.P.; Wijeyaratne, S.Chandrani (My University, 2009)
Bacterial populations were investigated in relation to the environmental parameters in Bolgoda Lake for a period of six months from January 2000 to June 2000. Surface water samples were collected from six sampling stations in the Bolgoda Lake at monthly intervals. Total viable bacterial colony forming units (assumed to be equal to the density of bacterial population), total coli forms and faecal coli forms were studied as biological indicators. Physico-chemical environment parameters included, temperature, pH, electrical conductivity, salinity, Secchi disk depth, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand(COD), orthophosphate and nitrate contents. These were measured using standard methods. Correlations among bacterial densities and selected water quality parameters were investigated, High densities of bacterial Gunatilaka and Wijeyaratne populations were recorded at several sampling points 111 the vicinity of outlet drains which bring domestic and industrial effluents. Low densities of bacterial populations were recorded in samples taken at up stream and down stream of the North Lake. Results also revealeJ that some chemical parameters may have an effect in the density of bacterial populations. Density of bacterial populations showed a significant negative correlation with Biochemical Oxygen demand (BOD) and with phosphate concentration. However, the density of bacterial population did not show a significant correlation with the nitrate content of the surface waters of the Lake. Further the DO, BOD values and P04- 3 content indicated organic and inorganic nutrient pollution of surface waters ofBolgoda Lake. However, samples collected from down stream had lower values for above parameters indicating that self- purification is taking place to a certain extent in the lake. However, results revealed that at present Bolgoda Lake is heavily exposed to pollution from industrial and residential effluents. To avoid catastrophe, measures should be taken to reduce pollution by curtailing sewage disposal and treatment of effluents of near by factories before being discharged into this Lake.
Keywords: Water quality; Bolgoda Lake; Evaluation of water quality